The effect of educational workshop on educational and informational skills of nurses in hospitals of Zahedan University of Medical Sciences, 2014 - Shahabi, Nahid; Rakhshani, Fatemeh (Researcher Bulletin of Medical Sciences, 2020)
Background & Aims: Providing qualified care service with proper education and information for clients is promising. Nurses are the primary providers of most health cares in the health system and they have a considerable power to affect the quality of health care. The purpose of this study is to assess the effect of educational workshop on educational and informational skills of nurses working in hospitals in Zahedan University of Medical Sciences. Materials & Methods: This research was conducted as semi-empirical with control group in April-May 2014. Samples included 181 nurses working in hospitals in Zahedan University of Medical Sciences. They were selected by random sampling from the list of nursing staffs in nursing office of aliIbn Abi Talib (98) and Khatam (83) hospitals. Questionnaire was developed based on expected skills for patient education. To determine the validity of the questionnaire, it was given to 8 experts and CVR and CVI were obtained as 0.93 and 0.89 and for reliability the Cronbach's alpha was 0.86. After the data collection phase, a workshop was held and after waiting two months, data was recollected. Results: The intervention increased scores of nurses, Informational skills 8% and educational skills 24%. Conclusion: Educational and informational skills, which are important factors in improving the quality of services delivery, can increase through effective educational interventions.